2008
DOI: 10.1021/nl802570m
|View full text |Cite
|
Sign up to set email alerts
|

Large-Scale Assembly of Silicon Nanowire Network-Based Devices Using Conventional Microfabrication Facilities

Abstract: We present a method for assembling silicon nanowires (Si-NWs) in virtually general shape patterns using only conventional microfabrication facilities. In this method, silicon nanowires were functionalized with amine groups and dispersed in deionized water. The functionalized Si-NWs exhibited positive surface charges in the suspensions, and they were selectively adsorbed and aligned onto negatively charged surface regions on solid substrates. As a proof of concepts, we demonstrated transistors based on individu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
89
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 121 publications
(92 citation statements)
references
References 33 publications
(66 reference statements)
0
89
1
Order By: Relevance
“…They can also be realized experimentally. Recent developments in various epitaxy techniques allowed also for the fabrication and design of quantum nanowire networks [9,10]. In 2004 Hul et al [11] showed that quantum graphs could be successfully simulated by microwave networks.…”
Section: Methodsmentioning
confidence: 99%
“…They can also be realized experimentally. Recent developments in various epitaxy techniques allowed also for the fabrication and design of quantum nanowire networks [9,10]. In 2004 Hul et al [11] showed that quantum graphs could be successfully simulated by microwave networks.…”
Section: Methodsmentioning
confidence: 99%
“…Controlled positioning of nanomaterials (e.g., nanotubes, nanowires, and nanoparticles) is an essential process for advances in nanoelectrical devices and photonic system [1][2][3][4]. In particular, selective and addressable deposition of SWCNTs is important for high-performance CNT based-electronic devices such as light-emitting diode, flexible display, conductive film, and transistor [5][6][7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…Several reports have demonstrated methods to assemble NWs into desired structures, including the electric/magnetic field assisted assembly method, 6,7) fluidic flow as-sembly method, [8][9] stick-slip motion method, 10,11) Langmuir-Blodgett method, [12][13][14][15] contact printing method, 16,17) and selection adhesion method. [18][19][20] Although such aforementioned methods have shown considerable progresses in assembling SiNWs into desired positions, they generally require unconventional facilities and sophisticated treatments which can be major problematic in cost-effectiveness and simplicity of the fabrication process.…”
Section: Introductionmentioning
confidence: 99%